Corporate realities : the dynamics of large and small organisations - Goffee, Robert; Scase, Richard (London ; New York : Routledge, 1995)
This book is about: The traditional entrepreneurial firm; Managing the creative and professional small business; From small to large: handling entrepreneurial growth; Manufacturing organisations; ...
Keywords: Management; Organization; Small business; Organizational behavior; Small business -- Management